Polyphenols from the mangosteen (Garcinia mangostana) fruit for breast and prostate cancer - Li, Gongbo; Thomas, Stacey P.; Johnson, Jeremy (Frontiers in Pharmacology, 2013)
The mangosteen (Garcinia mangostana) is a tropical fruit native to Southeast Asia and has long been reported to contain multiple health promoting properties. This fruit is an abundant source of xanthones, a class of polyphenolic compounds with a distinctive tricyclic aromatic ring system and is largely responsible for its biological activities including anti-cancer activity. Herein we describe the anti-cancer activity and mechanisms of mangosteen polyphenolic xanthones including α-Mangostin against breast cancer and prostate cancer. So far, extracts and individual xanthones have been found to induce apoptosis and inhibit proliferation on cancer cells in vitro and in vivo. Based on the reported finding there is clear evidence that these polyphenols target multiple signaling pathways involved in cell cycle modulation and apoptosis. Further work is required to understand its potential for health promotion and potential drug discovery for prostate and breast cancer chemoprevention.